Cutting Tools

JP7643089B2Active Publication Date: 2025-03-11MITSUBISHI MATERIALS CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021032270
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-02
Publication Date
2025-03-11
Estimated Expiration
2041-03-02

AI Technical Summary

Benefits of technology

【0013】 本発明に係る切削工具は、副硬質相の平均粒径を1.0μm以上、3.0μm以下とし、副硬質相の合計界面長に対する副硬質相-副硬質相粒界長の比率を10.0%未満とすることにより、耐塑性変形性が向上するため、連続旋削加工のような高負荷下での連続切削加工においても、長期の切削寿命を有するという顕著な効果を奏するものである。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643089000001
    Figure 0007643089000001
  • Figure 0007643089000002
    Figure 0007643089000002
  • Figure 0007643089000003
    Figure 0007643089000003
Patent Text Reader

Abstract

To provide a WC-based cemented carbide tool and a surface-coated WC-based cemented carbide tool that can exhibit excellent plastic deformation resistance in continuous cutting of alloy steel and the like.SOLUTION: A WC-based cemented carbide tool contains: at least one of Co and Ni of 4.0 mass% or more to less than 10.0 mass%; at least one selected from TiC, TaC, NbC, ZrC, HfC, and VC in total of 4.0 mass% or more to less than 12.0 mass%; Cr3C2 of 0.0 mass% or more to less than 0.5 mass%; and the balance being WC and inevitable impurities. Secondary hard phases have an average particle size of 1.0 μm or more to 3.0 μm or less. A ratio of the secondary hard phase-secondary hard phase intergranular length to a total interfacial length of the secondary hard phases is less than 10.0%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a WC-based cemented carbide cutting tool using, as a tool base, a WC-based cemented carbide that exhibits excellent resistance to plastic deformation in continuous cutting (e.g., continuous turning) of alloy steels and the like (steel, stainless steel, Ni-based alloys, etc.). [Background technology]

[0002] WC-based cemented carbide has high hardness and toughness, and therefore WC-based cemented carbide tools and surface-coated WC-based cemented carbide tools using this alloy as a base exhibit excellent wear resistance and are known as cutting tools having a long life over long periods of use. However, in recent years, various proposals have been made to further improve the cutting performance and tool life of WC-based cemented carbide tools depending on the type of work material, cutting conditions, etc.

[0003] For example, Patent Document 1 proposes that in a cemented carbide alloy having a main hard phase mainly composed of tungsten carbide and a binder phase mainly composed of an iron group element (including cobalt, the cobalt content of which is preferably 8 mass % or more in the cemented carbide alloy), when the number of tungsten carbide particles is A and the number of tungsten carbide particles having one or less contact points with other tungsten carbide particles is B, by satisfying B / A≦0.05, the plastic deformation resistance of the cemented carbide alloy is improved, and as a result, the life of a WC-based cemented carbide tool is extended in wet continuous cutting of carbon steel and stainless steel.

[0004] In Patent Document 2, in a WC-based cemented carbide tool containing 10 to 13 mass% Co, a ratio of 2 to 8% Cr to Co, at least one of TaC and NbC in a range such that the total amount of TaC and NbC is 0.2 to 0.5 mass%, with the remainder being WC, and having a hardness of 88.6 HRA to 89.5 HRA, it is proposed that the ratio D80 / D20 of the WC cumulative grain size 80% diameter D80 to the cumulative grain size 20% diameter D20 in the area ratio on the polished surface is set to a range of 2.0≦D80 / D20≦4.0, D80 is set to a range of 4.0 to 7.0 μm, and the WC adhesion degree c is set to 0.36≦c≦0.43, thereby preventing adhesion of the workpiece and improving chipping resistance in cutting difficult-to-cut materials such as stainless steel.

[0005] In Patent Document 3, the composition of the WC-based cemented carbide in a WC-based cemented carbide tool is WC-x mass %Co-y mass %Cr 3 C 2 -z When expressed in mass% VC, the following conditions are satisfied: 6≦x≦14, 0.4≦y≦0.8, 0≦z≦0.6, (y+z)≦0.1x. Also, the WC adhesion C of the WC-based cemented carbide is C=1-V b α When expressed as ·exp(0.391·L), the value of the binder phase volume fraction of the WC-based cemented carbide in this formula, V b is 0.11≦V b In addition, the value L of (standard deviation of WC particle size distribution) / (average WC particle size) is within the range of 0.3≦L≦0.7, and the coefficient α satisfies the value of 0.3≦α≦0.55. In this way, a WC-based cemented carbide tool has been proposed that has improved toughness and enhanced chipping resistance without reducing hardness and rigidity in cutting Al alloys, carbon steel, etc.

[0006] In Patent Document 4, when the length of the WC-WC adhesive interface in a WC-based cemented carbide tool is L1 and the length of the WC-Co adhesive interface is L2, R>(0.82-0.086×D)×(10 / V) It has been proposed that the thermal plastic deformation resistance and toughness of WC-based cemented carbide tools can be improved in cutting Ni-based heat-resistant alloys by satisfying the following equation. In addition, R = (L1) / ((L1)+(L2)) D: WC area average particle size (μm), which is in the range of 0.6≦D≦1.7. Here, the above D refers to the particle size of WC when the area ratio of WC is 50%. V: binder phase volume (vol%), which is in the range of 9≦V≦14.

[0007] Patent Document 5 proposes a WC-Co based cemented carbide part for cutting tools, which has a composition by weight consisting of Cr or / and Cr compounds: 0-4% (in terms of Cr), V or / and V compounds: 0-4% (in terms of V), TaC: 0-2%, TiC: 0-2%, N or / and N compounds: 0-1% (in terms of N), Co: 0.1-10%, WC and inevitable impurities: the remainder, and has a Co average thickness (CFP) of 0.06-30 nanometers, and is densified by applying a pressure of 3 atm to 200 atm using gas as a pressure medium in a part or the whole range of the temperature range of 900°C to 1600°C during heating during sintering. It is said that the toughness of this WC-Co based cemented carbide part, preferably an ultrafine grain low Co cemented carbide part having an average WC grain size of 1 μm or less and a CFP in the range of 0.06-30 nm, can be improved. Here, CFP is the average Co thickness (nm), The value was calculated from CFP=0.58*A / (100-A)*R, where A is Co (weight %) and 2R is WC average particle size (nm). [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2016-20541 A [Patent Document 2] JP 2017-88999 A [Patent Document 3] JP 2017-148895 A [Patent Document 4] JP 2017-179433 A [Patent Document 5] Japanese Patent Application Publication No. 7-305136 Summary of the Invention [Problem to be solved by the invention]

[0009] According to the conventional WC-based cemented carbide tools proposed in the above Patent Documents 1 to 5, the cutting performance and tool characteristics of the WC-based cemented carbide tools are improved by controlling the number of contact points between WC-WC particles, the particle size of the WC, the degree of WC adhesion, or manufacturing conditions, etc. However, when the conventional tools are used in continuous cutting of steel, alloy steel, stainless steel, and the like, particularly in continuous cutting under high load such as continuous turning, the plastic deformation resistance of the base body is insufficient, and the occurrence of tool deformation and the like cannot be sufficiently suppressed, resulting in a problem that the tool reaches the end of its life. [Means for solving the problem]

[0010] In order to develop a WC-based cemented carbide tool that exhibits excellent resistance to plastic deformation in continuous cutting processes under high loads, such as continuous turning processes of steel, alloy steel, stainless steel, and the like, the present inventors have changed their perspective from that of conventional techniques and conducted intensive research focusing on the grain boundary length and interface length related to the secondary hard phase of a WC-based cemented carbide, i.e., the length of the interface where a secondary hard phase contacts a main hard phase (hereinafter referred to as the "secondary hard phase-main hard phase interface length"), the length of the grain boundary where a secondary hard phase contacts another secondary hard phase (hereinafter referred to as the "secondary hard phase-secondary hard phase grain boundary length"), and the length of the interface where a secondary hard phase contacts a binder phase (hereinafter referred to as the "secondary hard phase-binder phase interface length"), and have conducted research focusing on the morphology of the grain boundaries and interfaces, including the length of the interface where a secondary hard phase contacts a binder phase (hereinafter referred to as the "secondary hard phase-binder phase interface length"). As a result, the following findings were obtained.

[0011] That is, the present inventors have found that, when cutting accompanied by plastic deformation is performed, if the ratio of the "secondary hard phase-secondary hard phase grain boundary length" to the sum of the "secondary hard phase-main hard phase interface length", the "secondary hard phase-secondary hard phase grain boundary length", and the "secondary hard phase-bonding phase interface length" (also referred to as the "total interface length of secondary hard phases") is 10.0% or more, cavities are preferentially generated at the secondary hard phase-secondary hard phase grain boundary, resulting in large plastic deformation and a short life. The inventors have addressed this issue by adjusting the component composition of the WC-based cemented carbide, producing a coarse solid solution, and then distributing the secondary hard phases having large crystal grain sizes with good dispersibility by, for example, ball mill mixing, and further setting the ratio of 2) "secondary hard phase-secondary hard phase grain boundary length" to the total length of the secondary hard phases, which is the total of 1) "secondary hard phase-main hard phase interface length", 2) "secondary hard phase-secondary hard phase grain boundary length", and 3) "secondary hard phase-bonding phase interface length", to less than 10.0%, thereby solving the issue of the present invention of deterioration in plastic deformation resistance. The WC-based cemented carbide according to the present invention comprises a main hard phase containing WC, a secondary hard phase containing at least one selected from the group consisting of TiC, TaC, NbC, ZrC, HfC, and VC, and a binder phase containing Co and / or Ni.

[0012] The present invention has been made based on the above findings and is as follows. "(1) In a cutting tool made of WC-based cemented carbide having a WC-based cemented carbide as a substrate, The composition of the WC-based cemented carbide contains at least one of Co and Ni in an amount of 4.0% by mass or more and less than 10.0% by mass, In addition, at least one selected from TiC, TaC, NbC, ZrC, HfC, and VC is contained in a total amount of 4.0 mass% or more and less than 12.0 mass%; In addition, Cr 3 C 2 Contains 0.0% by mass or more and less than 0.5% by mass, The balance is composed of WC and unavoidable impurities. The average grain size of the secondary hard phase is 1.0 μm or more and 3.0 μm or less, A cutting tool made of WC-based cemented carbide, characterized in that the ratio of a secondary hard phase-secondary hard phase grain boundary length to a total interface length of the secondary hard phases is less than 10.0%. (2) A surface-coated WC-based cemented carbide cutting tool, characterized in that a hard coating layer is formed on the cutting edge of the WC-based cemented carbide cutting tool according to (1) above." In addition, TiC, TaC, NbC, ZrC, HfC, VC, and Cr in (1) and (2) above 3 C 2 The contents are values ​​calculated as carbides for the amounts of Ti, Ta, Nb, Zr, Hf, V, and Cr measured on a cross section of the WC-based cemented carbide alloy. In addition, in this specification, when a numerical range is indicated using "to", it means that the lower limit and upper limit of the numerical range are included. Effect of the Invention

[0013] The cutting tool according to the present invention has an average grain size of the secondary hard phases of 1.0 μm or more and 3.0 μm or less, and a ratio of the secondary hard phase-secondary hard phase grain boundary length to the total interface length of the secondary hard phases of less than 10.0%, thereby improving resistance to plastic deformation, and thus exhibiting the remarkable effect of providing a long cutting life even in continuous cutting processes under high loads, such as continuous turning processes. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The composition of each component constituting the WC-based cemented carbide according to the present invention and the structure of the cemented carbide (binder phase, main hard phase, secondary hard phase) will be described below.

[0015] 1.WC-based cemented carbide composition The composition of the cemented carbide constituting the cutting tool of this embodiment is: Co and / or Ni, 4.0% by mass or more and less than 10.0% by mass, One or more of TiC, TaC, NbC, ZrC, HfC, and VC are 4.0 mass% or more and less than 12.0 mass%. Cr3 C 2 in an amount of 0.0 mass % or more and less than 0.5 mass %, with the remainder consisting of WC and unavoidable impurities. The following explains each in order.

[0016] (1) Co, Ni Co and Ni are the main components of the binder phase in the WC-based cemented carbide. It is preferable that the cutting tool contains one or both of Co and Ni as the main components, and the total content of Co and Ni is 4.0 mass% or more and less than 10.0 mass% of the entire cutting tool. Here, the term "main component" refers to a composition in which either one or both of Co and Ni are contained in a total amount of 50 at % or more relative to all components forming the binder phase. The binder phase may contain at least one of Ti, Ta, Nb, Zr, Hf, and V. When these elements are present in the binder phase, they are presumed to be in a state of solid solution in the binder phase. Furthermore, the binder phase may contain W and C, which are components of the main hard phase, and other unavoidable impurities. The at% of Co and Ni can be determined by mirror-finishing any surface or cross section of the cemented carbide and subjecting the machined surface to fluorescent X-ray diffraction measurement.

[0017] (2)Cr 3 C 2 Cr 3 C 2 It dissolves as Cr in Co, which forms the main binder phase, inhibits the growth of the WC phase, which forms the main hard phase, refines the grain size of the WC phase, gives the WC-based cemented carbide a fine and uniform grain structure, and has the effect of increasing toughness and improving plastic deformation resistance. 3 C 2 If the content exceeds 5% relative to the Co content, composite carbides of Cr and W are precipitated, which reduces toughness and may become the starting point for the generation of chipping. In the present invention, Cr is not an essential component. However, since the upper limit of the Co content is less than 10.0 mass%, the content ratio of Cr, when added, to the entire cutting tool is 10.0 mass%. 3C 2 It is preferable to add less than 0.5 mass % in terms of the converted amount.

[0018] (3) TiC, TaC, NbC, ZrC, HfC and VC TiC, TaC, NbC, ZrC, HfC and VC are contained in the WC-based cemented carbide as main secondary hard phase forming components, and the total content of one or more of these components is 4.0 mass% or more and less than 12.0 mass%. When these carbides are present, it is preferable that the content of one or more compounds represented by MC is less than a maximum of 12.0 mass% based on the entire cutting tool, assuming that the carbide is a 1:1 bond between M (metal atom) and C. That is, if it is 12.0% by mass or more, the wear resistance becomes insufficient and agglomerates are easily formed, which become the starting point for the occurrence of chipping, so that it is preferable to keep the content in the range of less than 12.0% by mass. Furthermore, if the average grain size of the secondary hard phases formed by these carbides is less than 1.0 μm, the secondary hard phases are likely to slip between each other during cutting, resulting in insufficient resistance to plastic deformation and chipping. On the other hand, if the average grain size exceeds 3.0 μm, sufficient wear resistance cannot be obtained. Therefore, it is preferable to select the grain size from the range of 1.0 μm or more and 3.0 μm or less. The average grain size of the secondary hard phases is determined by mirror-finishing any surface or cross section of the cemented carbide, observing the machined surface at pixel size by electron backscatter diffraction (EBSD), determining the area of ​​at least 300 secondary hard phases by image analysis, and calculating the diameter of a circle equal to the area, and averaging the results. For the mirror finishing, for example, a focused ion beam device (FIB device), a cross-section polisher device (CP device), or the like is used.

[0019] (4) WC WC is contained as a main hard phase forming component of the WC-based cemented carbide. The main hard phase may contain unavoidable impurities that are inevitably mixed in during the manufacturing process. If the average grain size of the main hard phase containing WC, which is the main hard phase forming element, is less than 0.2 μm, the main hard phases are likely to slip during cutting, resulting in insufficient resistance to plastic deformation and chipping. On the other hand, if the average grain size exceeds 4.0 μm, sufficient wear resistance cannot be obtained. Therefore, it is preferable to select the grain size from the range of 0.2 μm or more and 4.0 μm or less. The average grain size of the main hard phases, like that of the secondary hard phases, is determined by mirror-finishing any surface or cross section of the cemented carbide, observing the machined surface at pixel size by electron backscatter diffraction (EBSD), determining the area of ​​at least 300 main hard phases by image analysis, and averaging the diameters of circles equal to the areas. For the mirror finishing, for example, a focused ion beam device (FIB device), a cross-section polisher device (CP device), or the like is used.

[0020] (5) Inevitable impurities As described above, the secondary hard layer, the main hard phase, and the binder phase may contain impurities that are inevitably mixed in during the manufacturing process, and the amount of such impurities is preferably 0.3% by mass or less, with the total mass of the cutting tool being 100%.

[0021] 2. Method for deriving the ratio of secondary hard phase-secondary hard phase grain boundary length to the total interface length of secondary hard phases The ratio of the grain boundary length of the secondary hard phase to the total boundary length of the secondary hard phase is derived, for example, by simultaneously capturing EBSD (Electron Back Scattered Diffraction) patterns and EDS (Energy Dispersive X-ray Spectroscopy) data using an OIM Data Collection (OIM crystal orientation analyzer) manufactured by TSL. For each crystal grain, the EDS count values ​​obtained from each measurement point inside the crystal grain corresponding to each element are averaged to obtain the EDS measurement value for each element of each crystal grain, and the composition of each crystal grain is derived from the obtained measurement value. From the EBSD pattern, crystal grains identified as HCP phases and containing 20 at% or more of W are defined as WC grains, and among crystal grains identified as FCC phases, particles having a total content of Co and Ni of 50 at% or more are defined as binder phases, and particles having a total content of Co and Ni of less than 50 at% are defined as secondary hard phases. The total interface length of the secondary hard phases is defined as the total length of the secondary hard phase-main hard phase interface length, the secondary hard phase-secondary hard phase grain boundary length, and the secondary hard phase-binder phase interface length, and the secondary hard phase-secondary hard phase grain boundary length is divided by the total interface length of the secondary hard phases to obtain the secondary hard phase-secondary hard phase grain boundary length ratio. The observation field is set to have a size of 20 μm (vertical) × 70 μm (horizontal) and a pixel size of 40 nm (vertical) × 40 nm (horizontal).

[0022] The WC-based cemented carbide tool and the surface-coated WC-based cemented carbide tool of the present invention will be specifically described below with reference to examples, although the present invention is not limited to these examples. EXAMPLES

[0023] <WC-based carbide tool of the present invention> (a) Blend with raw powder The raw material powders were WC powder with an average particle size (d50) of 2.5 μm to 6.5 μm, Co powder, Ni powder, and Cr powder, each of which had an average particle size (d50) in the range of 1.0 to 3.0 μm. 3 C 2 Powder, TiC powder, TaC powder, NbC powder, ZrC powder, HfC powder, and VC powder were prepared. First, among these powders, TiC powder, TaC powder, NbC powder, ZrC powder, HfC powder, and VC powder, which are carbides of secondary hard phase forming elements, were weighed out to a predetermined composition, mixed in a ball mill for 24 hours, heat treated in a vacuum at 1600°C for 4 hours, and then crushed in a ball mill for 1 hour to produce a coarse solid solution powder (see the column for solid solution powder in Table 1).

[0024] (b) Mixing and sintering process The obtained coarse solid solution powder was then mixed with the WC powder, Co powder, Ni powder and Cr powder. 3 C 2 The powder was mixed with the mixture and wet mixed at 500 RPM for 1 hour using an attritor, the resulting slurry was dried and then pressed at a pressure of 100 MPa, and the resulting green compact was sintered to produce a sintered body (see the column for blend composition in Table 1 and the column for the process of the present invention in Table 3).

[0025] 1) Heating process First, in the temperature increase process from 1000°C, which is the solid-phase sintering temperature, to 1350°C, the sintering temperature, the temperature increase rate was increased to 40°C / min or more to suppress solid-phase sintering.

[0026] 2) Sintering process Next, in the sintering step, the temperature was raised to 1350° C. or higher, and then the temperature was kept at 1350° C. to 1450° C. for 10 to 80 minutes under a vacuum of 0.1 Pa or less, thereby obtaining a sintered body of a WC-based cemented carbide. In the WC-based cemented carbide sintered body obtained by this sintering process, the secondary hard phases having large crystal grain sizes are well dispersed in the sintered body, which makes it possible to reduce the ratio of the grain boundary length between secondary hard phases to the total interface length of the secondary hard phases. This makes it possible to reduce the occurrence of cavities at the grain boundaries between secondary hard phases, thereby achieving excellent resistance to plastic deformation.

[0027] Next, the WC-based cemented carbide sintered body was machined and ground to have a shape of CNMG432MM, to produce cemented carbide substrates 1 to 10 shown in Table 4 (hereinafter referred to as inventive tool substrates 1 to 10).

[0028] ≪Comparative example WC-based carbide tool≫ For comparison, comparative cemented carbide substrates 1 to 8 (hereinafter referred to as comparative tool substrates 1 to 8) were prepared. (a) Blend with raw powder The raw material powders were WC powder with an average particle size (d50) of 2.5 μm to 6.5 μm, Co powder, Ni powder, and Cr powder, each of which had an average particle size (d50) in the range of 1.0 to 3.0 μm. 3 C 2 Powder, TiC powder, TaC powder, NbC powder, ZrC powder, HfC powder, and VC powder were prepared.

[0029] Next, these powders were mixed to obtain the composition shown in Table 2 to prepare sintering powder, which was then wet-mixed for 1 hour at a rotation speed of 500 rpm using an attritor. After drying, the mixture was press-molded at a pressure of 100 MPa to produce a powder compact. Next, sintering was performed under sintering process conditions of comparative processes 1' to 8' shown in Table 3, which were different from at least one of the sintering process conditions of the tool bases 1 to 10 of the present invention (heating rate of 40°C / min or more, sintering temperature of 1350 to 1450°C, and sintering time of 10 to 80 minutes) to obtain WC-based cemented carbide sintered bodies. The WC-based cemented carbide sintered bodies were then machined and ground to have a shape of CNMG432MM, to produce comparative example tool bases 1 to 8 shown in Table 5.

[0030] For the cross sections of the cemented carbide of the tool bases 1 to 10 of the present invention and the comparative tool bases 1 to 8, the content of each element constituting the alloy was measured by an electron microanalyzer (EPMA) over an entire field of view of 60 μm (vertical) × 90 μm (horizontal), with ten fields of view being measured so that no fields of view overlapped with each other, and the average value was taken as the content of each component. The contents of the elements Cr, Ti, Ta, Nb, Zr, Hf and V were calculated by converting them into carbides. Tables 4 and 5 show the average contents of each element.

[0031] Next, for the cross sections of the WC-based cemented carbide of the present invention tools 1 to 10 and the comparative example tools 1 to 8, the EBSD patterns and the obtained EDS data were simultaneously captured using, for example, the OIM crystal orientation analyzer.

[0032] Next, for each crystal grain, the EDS count values ​​obtained from each measurement point inside the crystal grain corresponding to each element were averaged to obtain the EDS measurement value for each element of each crystal grain, and the composition of each crystal grain was derived from the obtained measurement values. Among the crystal grains identified as FCC phase from the EBSD pattern, particles with a total Co and Ni content of 50 at% or more were defined as binder phases, and particles with a total Co and Ni content of less than 50 at% were defined as secondary hard phases. The total interface length of the secondary hard phases was defined as the sum of the secondary hard phase-main hard phase interface length, the secondary hard phase-secondary hard phase grain boundary length, and the secondary hard phase-binder phase interface length, and the secondary hard phase-secondary hard phase grain boundary length was divided by the total interface length of the secondary hard phases to obtain the secondary hard phase-secondary hard phase grain boundary length ratio. The observation field was set to have a size of 20 μm (vertical) × 70 μm (horizontal) and a pixel size of 40 nm (vertical) × 40 nm (horizontal).

[0033] [Table 1]

[0034] [Table 2]

[0035] [Table 3]

[0036] [Table 4]

[0037] [Table 5]

[0038] The above-mentioned tools 1 to 10 of the present invention and comparative tools 1 to 8 were subjected to the following wet continuous turning test while each tool was screwed to the tip of a tool steel bit using a fixing jig. Work material: JIS SUS304 (HB170) round bar, Cutting speed: 110m / min, Cutting depth: 2.0mm, Feed: 0.6mm / rev, Cutting time: 4 minutes, Uses wet water-soluble cutting oil. After the wet continuous cutting test, the amount of plastic deformation of the cutting edge was measured and the wear state of the cutting edge was observed. The amount of plastic deformation of the cutting edge was measured by drawing a line segment on the ridge where the rake face intersects with the flank face of the main cutting edge of the tool at a position sufficiently distant from the cutting edge, extending the line segment toward the cutting edge, and measuring the maximum distance between the extended line segment and the ridge line of the cutting edge (perpendicular to the extended line segment). When the amount of plastic deformation of the flank face was 0.04 mm or more, the wear state was determined to be cutting edge deformation. Table 7 shows the results of this test.

[0039] [Table 6]

[0040] In addition, hard coating layers having average thicknesses shown in Table 8 were formed by PVD or CVD on the cutting edge surfaces of the tools 1 to 4 of the present invention and the comparative tools 1 to 4, to produce surface-coated WC-based cemented carbide cutting tools 1 to 4 of the present invention (hereinafter referred to as "coated tools of the present invention") and comparative surface-coated WC-based cemented carbide cutting tools 1 to 4 of the comparative examples (hereinafter referred to as "coated tools of the comparative examples"). For each of the above-mentioned coated tools, the following wet continuous cutting test was carried out to measure the amount of plastic deformation on the flank of the cutting edge and to observe the state of wear of the cutting edge. Cutting conditions: Work material: JIS SUS304 (HB170) round bar, Cutting speed: 235m / min, Cutting depth: 2.0mm, Feed: 0.6mm / rev, Cutting time: 5 minutes, Uses wet water-soluble cutting oil. Table 9 shows the results of the cutting tests.

[0041] [Table 7]

[0042] [Table 8]

[0043] The test results shown in Tables 6 and 8 show that the tools of the present invention and the coated tools of the present invention exhibit excellent resistance to plastic deformation without the occurrence of fracture, whereas the comparative tools and the comparative coated tools have a short tool life due to the occurrence of fracture or plastic deformation. [Industrial Applicability]

[0044] As described above, the tool and the coated tool of the present invention exhibit excellent effects over long periods of use in heavy-duty continuous cutting, such as continuous turning of alloy steel, stainless steel, etc., and greatly contribute to extending the tool life.

Claims

1. In a WC-based cemented carbide cutting tool having a WC-based cemented carbide substrate, The WC-based cemented carbide contains at least one of Co and Ni in an amount of 4.0% by mass or more and less than 10.0% by mass, Also, at least one selected from TiC, TaC, NbC, ZrC, HfC, and VC is contained in a total amount of 4.0 mass% or more and less than 12.0 mass%, In addition, Cr 3 C 2 Contains 0.0% by mass or more and less than 0.5% by mass, The balance is made up of WC and unavoidable impurities. The average grain size of the secondary hard phase is 1.0 μm or more and 3.0 μm or less, A WC-based cemented carbide cutting tool, characterized in that the ratio of a secondary hard phase-secondary hard phase grain boundary length to a total interface length of the secondary hard phases is less than 10.0%.

2. 2. A surface-coated WC-based cemented carbide cutting tool according to claim 1, further comprising a hard coating layer formed on a cutting edge of the WC-based cemented carbide cutting tool.

Citation Information

Patent Citations

  • Cemented carbide parts

    JP1995305136A

  • Super hard alloy and cutting tool

    JP2016020541A

  • Hard metal alloy, tool for cutting work using the same and insert for milling work

    JP2017088999A

  • WC-based cemented carbide drill excellent in breakage resistance

    JP2017148895A

  • WC-based hard metal alloy-made tool excellent in thermal resisting plastic deformation property

    JP2017179433A